(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the assessment of production break-even by the CVP-analysis method, which helps to understand the relationship "cost-volume-profit". The methodology for calculating the break-even point is investigated, which is based on the marginal approach to consider the costs of the enterprise.